2006
DOI: 10.1021/jo060652r
|View full text |Cite
|
Sign up to set email alerts
|

Interconversion of Bicyclo[2.2.1]hept-2-yne and 5-Bicyclo[2.1.1]hexylidenecarbene

Abstract: This work provides unambiguous results for the full equilibration of cycloalkyne 2 with its isomeric ring-contracted vinylidene 3 prior to their reaction with 2,3-dihydropyran (4), as evidenced by the products formed when 2 and 3 are produced directly from their precursors having bicyclo[2.2.1]heptyl and bicyclo[2.1.1]hexyl skeletons, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…68 The interconversion of bicyclo[2.2.1]hept-2-yne (86) and 5-bicyclo[2.1.1]hexylidenecarbene (87) has been studied. 69 The authors claim that their results, in combination with those of an earlier study, give unambiguous support for a rapid equilibrium between the cycloalkyne and the carbene. The results presented comprise careful analysis of product mixtures.…”
Section: Rearrangementmentioning
confidence: 58%
See 1 more Smart Citation
“…68 The interconversion of bicyclo[2.2.1]hept-2-yne (86) and 5-bicyclo[2.1.1]hexylidenecarbene (87) has been studied. 69 The authors claim that their results, in combination with those of an earlier study, give unambiguous support for a rapid equilibrium between the cycloalkyne and the carbene. The results presented comprise careful analysis of product mixtures.…”
Section: Rearrangementmentioning
confidence: 58%
“…55 Better yields and ees are achieved for tricycles (69) derived from furan than for (68) derived from more bulky pyrroles. Monocycloee propanation (with high yields and ees) is achieved on the furan ring of benzofuran, whereas double cyclopropanation of the indole is observed.…”
Section: Enhancing the O-h Insertion]mentioning
confidence: 99%
“…In support of the racemization, Gassman and co-workers discerned the formation of highly strained bicyclo[2.2.1]­heptyne (norbornyne) akin to 11 . More recently, Gilbert and co-workers demonstrated , that norbornyne acts more as a dicarbene that is in equilibrium with alkylidenecarbene 12 (Figure E). Both Komatsu’s and Hart’s research groups confirmed the transient formation of bicyclo[2.2.2]­octynes by trapping them with 1,3-diphenylisobenzofuran .…”
Section: Resultsmentioning
confidence: 96%